Citra Tokoh Sutik dalam Novel Burung Burung Migran Karya Miranda Harlan dan Sutik AS (Kajian Perspektif Feminisme) - Yuliana Fitrianita Kurnia; Harun Ahmad Sengaji (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2019)
The novel Burung-Burung Migran created by Miranda Harlan and Sutik AS reveals female power in a way she deals with how hard a life could be. Sutik’s character which portrayed in the novel is suitable to be viewed from feministic perspective. Therefore, the study was taken, besides explaining the structure of the novel, also to explain, in particularly, the image of Sutik’s character in the Burung-Burung Migran’s novel viewed from feministic perspective. The object studied from this novel was about the structure of the novel itself, which divided into three elements; the background, characterization, and the plot of the story. However, Sutik’s characterization was analyzed through three different aspects, physically, psychologically, and socially. This literature study of Burung-Burung Migran applies descriptive qualitative method with feministic ideological mode of literature critics approach. It uses a written form source, taken from the novel “Burung-Burung Migran” by Miranda Harlan and Sutik AS. The data is collected through a literature study and analyzed through several steps, which are (a) data selection, (b) identification and classification of the data, (c) data interpretation, which finally ends in the drawing of conclusion. The result of the study shows that the structure of the novel, “Burung-Burung Migran”, considered from the background, has nine place settings, eight time settings, and five social settings. It has ten characters, which are prominent in the story, also has fifty-five other characters. Considered from the plotting, it uses back-and-forth flow of ideas, which has four climaxes of different stages. However, the image of Sutik’s character is divided into three different aspects, they are one physical aspect, five psychological aspects, and her social aspect is subdivided into three aspects of hers in the family and three others in the society. My suggestion is that another study needs to be conducted towards this novel, from feministic gynocritics perspective. In addition to that point, in order to achieve the best result in conducting a feminist literature study, the appropriate choice of data source is a necessity.